2004
DOI: 10.1002/chin.200414129
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Aminopyrrolidine Derivatives as Melatoninergic Agents.

Abstract: Heterocyclic Aminopyrrolidine Derivatives as Melatoninergic Agents. -The synthesis of a series of chiral aminopyrrolidine derivatives [cf. (VIII), (X)] as novel melatoninergic ligands is described. Urea derivative (Xa), the most potent compound, is identified as an orally bioavailable agonist at MT1 and MT2 melatonin receptors with low vasoconstrictive activity. -(SUN*, L.-Q.; et al.; Bioorg. Med. Chem. Lett. 13 (2003) 24, 4381-4384; Bristol-Myers Squibb Pharm. Res. Inst., Wallingford, CT 06492, USA; Eng.) -D.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Two independent studies have shown that K63 polyubiquitination by Ubc13/Uev1A is required for the activation of IKK by BCL10 and MALT1. 42,43 Both studies showed that NEMO is a ubiquitination target, but they differed in the identity of the E3 that catalyzes NEMO polyubiquitination. One study showed that MALT1 is a ubiquitin E3 although it lacks any known E3 domain such as the RING domain.…”
Section: The Role Of Ubiquitination and Tak1 In Adaptive Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Two independent studies have shown that K63 polyubiquitination by Ubc13/Uev1A is required for the activation of IKK by BCL10 and MALT1. 42,43 Both studies showed that NEMO is a ubiquitination target, but they differed in the identity of the E3 that catalyzes NEMO polyubiquitination. One study showed that MALT1 is a ubiquitin E3 although it lacks any known E3 domain such as the RING domain.…”
Section: The Role Of Ubiquitination and Tak1 In Adaptive Immunitymentioning
confidence: 99%
“…42 The other study showed that MALT1 binds to TRAF6, which then serves as a ubiquitin E3 to polyubiquitinate NEMO. 43 The latter study also employed in vitro reconstitution and RNAi experiments in Jurkat T cells to show that TAK1 is required for IKK activation in the TCR pathway. RNAi of both TRAF2 and TRAF6 led to more potent inhibition of IKK than RNAi of TRAF2 or TRAF6 alone, suggesting that these proteins may function redundantly in T cells.…”
Section: The Role Of Ubiquitination and Tak1 In Adaptive Immunitymentioning
confidence: 99%
“…Interestingly, recent reports also suggest that proteasome function may be inhibited during apoptosis through targeting of several proteasome subunits for caspase-dependent proteolysis. 27,28 However, proteasomes have also been implicated in the regulation of apoptosis in more specific ways. The inhibitor of apoptosis proteins (IAPs) are a family of caspase inhibitors that can delay apoptosis upon overexpression in a variety of cell types.…”
Section: The Ub-proteasome System and Apoptosismentioning
confidence: 99%
“…HA is responsible for the binding association of MN and CN. MN discovers HA with the secured Dynamic Home Agent Address Discovery mechanism (DHAAD) [4]. HA maintains the HA list which includes the link address of all the HAs within the network along with its preference value.…”
Section: Introductionmentioning
confidence: 99%